Differential modulation of glial cell mediated neuroinflammation in Plasmodium berghei ANKA infection by TGF β and IL 6. (November 2017) - Sarkar, Samrat; Keswani, Tarun; Sengupta, Anirban; Mitra, Soham; Bhattacharyya, Arindam
Graphical abstract: Highlights: IL 6 and TGF β are playing differential role in PbA infected mice brain. IL 6 depletion reduces level of glial cell activation mediated neuroinflammation. IL 6 depletion can be exploited in combination with an anti sequestrating agent. Abstract: Modulation of pro-inflammatory and anti-inflammatory axis and orientation of glial cell function towards neuroinflammation, were hallmark signs of cerebral malaria (CM). CM pathogenesis was concerned with the circulating levels of Interleukin 6 (IL 6) and Transforming growth factor β (TGF β). Definite roles of these two cytokines in brain related pathology remained largely unexplored. To study the effect of these two cytokines, we have examined changes in morphology and in activation profile of the glial cells after TGF β and IL 6 neutralization during CM in cortex and cerebellum of the Plasmodium berghei ANKA (PbA) infected male swiss albino mice. PbA infection caused severe inflammation by inducing changes in morphological features as well as in activation profile of the astrocytes and microglia. Similar inflammatory signs were evident in Anti TGF β treated set. Interestingly in the Anti IL 6 treated set, reduced level of activation of these glial cells corresponds to the reduced level of inflammatory profile. Microglial activation was found to be synchronous with TLR4 engagement. Neuronal death was triggered by neuroinflammatory milieu seen in PbA and PbA + Anti TGF β treated set. In conclusion, it can be said that IL 6 and TGF β perform essential role in CM pathogenesis by modulating the level of glial cell induced neuroinflammation.